Answer:
[tex](\frac{f}{g})(x)=4[/tex]
Step-by-step explanation:
(f/g)(x) means to divide f(x) by g(x) and get the expression. We will do this and see if we can simplify the algebraic ratio. Shown below is the process:
[tex]\frac{f}{g}(x)=\frac{f(x)}{g(x)}\\=\frac{16x+12}{4x+3}[/tex]
We can take 4 as common from the numerator, so it becomes:
[tex]\frac{16x+12}{4x+3}\\=\frac{4(4x+3)}{4x+3}[/tex]
"4x+3" gets cancelled out from both denominator and numerator, thus we have:
[tex]\frac{4(4x+3)}{4x+3}\\=4[/tex]
4 is the correct expression for (f/g)(x).